Determinants of Employee Performance: A Study at Makhad Al-Jamiah IAIN Langsa - Asran, Muhammad; Harahap, Syahwin; Fauzi, Marwan; Frananda, Mhd; Bernadin, Avelina Anindtya; Sadli, Efendi (Jurnal EMT KITA, 2025)
This study aims to analyze the factors that affect employee performance at Makhad Al-Jamiah IAIN Langsa. Employee performance is a crucial element in supporting the achievement of organizational goals, especially in Islamic-based educational institutions. This study uses a quantitative approach with a survey method, involving 110 employees as respondents. Data was collected through questionnaires that included variables such as competence, motivation, leadership, work environment, and career development. Data analysis was carried out using descriptive statistical methods and multiple regression to determine the influence of each factor on employee performance. The results of the study show that employee competence has a significant influence on performance, where the improvement of skills and work knowledge is directly correlated with productivity. Motivation, both intrinsic and extrinsic, is also the dominant factor that determines the extent to which employees are willing to make the best contribution. Transformational leadership has been proven to be able to create a conducive work environment, increase morale, and encourage innovation. In addition, facilities and support in the work environment play an important role in ensuring employee comfort and efficiency. Career development through training and job guidance has a positive impact on loyalty and performance.